Cigarette smoke exposure and personal hygiene as determinants for cervical pre-cancer lession in Denpasar, 2012 - I Gusti Agung Ayu Novya Dewi; Anak Agung Sagung Sawitri; I Nyoman Adiputra (Universitas Udayana, 2013)
The prevalence of cervical cancer in Bali continues to rise (43/100.000 and in the Denpasar City is 25/100.000 in 2010). The cervical pre-cancer cases are greater of 184/100.000, eight times the number of cervical cancer cases. Pre-cancer lesion can be detected early using visual inspection of acetic acid. This study aims to explore the risk factors of self hygiene and exposure to cigarette smoke for the incidence of cervical pre-cancer lesions. This case-control study involved 60 cases and 60 controls taken from the referral registery during August 2010-December 2011. Study was conducted in two public health centres that offer early detection using visual inspection of acetic acid services in Denpasar. Respondents were interviewed using a modified See and Treat questionnaire. Data were analised using univariate, bivariate with chi square test and multivariate (logistic regression) in order to determine the most dominant risk factor. Respondents were aged 24-56 years, with mean of 41.76 years. The majority of respondents is high school graduated (87.5%), private sector employment (47.5%), the age of first marriage was >20-25 years (41.7%), parity was 2 (42.5%) and most (83.3%) did not have a family history of cancer. The study reveals that poor hygiene increased cervical pre-cancer lessions by 29 times [OR=29.57; 95%CI: 10.51-83.17]. Out of eight indicators for personal hygiene, the frequency of sanitary pads changing has the highest risk (16.44). An exposure to cigarette smoke for >4 hours/day increases cervical pre-cancer lessions by 4 times [OR=4.75; 95%CI: 2.19-10.33]. From the logistic regression analysis, personal hygiene is the most dominant risk factors. The two most significant variables in increasing risk factor for cervical precancer lesions were exposure to cigarette smoke and personal hygiene. Further attention must be paid to personal hygiene including regularity and choice of sanitary pads.